Effects of a 6-month self-rehabilitation programme in addition to botulinum toxin injections and conventional physiotherapy on limitations of patients with spastic hemiparesis following stroke (ADJU-TOX): protocol study for a randomised controlled, investigator blinded study. Issue 8 (30th August 2018) - Bonnyaud, Celine; Gallien, Philippe; Decavel, Pierre; Marque, Philippe; Aymard, Claire; Pellas, Frédéric; Isner, Marie-Eve; Boyer, François Constant; Muller, François; Daviet, Jean-Christophe; Dehail, Patrick; Perrouin-Verbe, Brigitte; et al.
Abstract : Introduction: Home-based self-rehabilitation programmes combined with botulinum toxin injections (BTIs) appear to be a relevant approach to increase the recommended intensive rehabilitation of patients with spasticity following a stroke. The literature highlights a lack of evidence of beneficial effects of this adjuvant therapy to reduce limitations of patients with stroke. The aim of this study is to assess the effects of a 6-month self-rehabilitation programme in adjunction to BTI, in comparison with BTI alone, to reduce limitations of patients with spasticity following a stroke. Methods and analysis: 220 chronic patients will participate to this multicentre, prospective, randomised, controlled, assessor blinded study. All patients will benefit from two successive BTI (3 months apart), and patients randomised in the self-rehabilitation group will perform in adjunction 6 months of self-rehabilitation at home. All patients continue their conventional physiotherapy. The main outcome is the primary treatment goal (PTG), which will be determined jointly by the patient and the medical doctor using Goal Attainment Scaling. Impairments and functions, quality of life, mood and fatigue will be assessed. Botulinum toxin will be injected into the relevant muscles according to the PTG. Patients in the self-rehab group will be taught the self-rehabilitation programme involving respectively 10 min of stretching, 10 min of strengthening and 10 min of task-oriented exercises, corresponding to their PTG. Compliance to the self-rehabilitation programme will be monitored. Ethics and dissemination: Patients will sign written informed consent. Ethical approval was obtained from ethics committee. The results will be disseminated in a peer-reviewed journal and presented at international congresses. The results will also be disseminated to patients. Trial registration number: NCT02944929.